The Government Budget: An Overlooked Vehicle for Advancing Strategic Health Purchasing - Aloysius Ssennyonjo; Otieno Osoro; Freddie Ssengooba; Elizabeth Ekirapa-Kiracho; Chrispus Mayora; Richard Ssempala; Danielle Bloom (Taylor & Francis Group, 2022)
ABSTRACTThe most effective way to finance universal health coverage (UHC) is through compulsory prepaid funds that flow through the government budget. Public funds-including on-budget donor resources-allow for pooling and allocation of resources to providers in a way that aligns with population health needs. This is particularly important for low-income settings with fiscal constraints. While much attention is paid to innovative sources of additional financing for UHC and to implementing strategic purchasing approaches, the government budget will continue to be the main source of health financing in most countries-and the most stable mechanism for channeling additional funds. The government budget should therefore be front and center on the strategic purchasing agenda. This commentary uses lessons from Tanzania and Uganda to demonstrate that more can be done to use the government budget as a vehicle for making health purchasing more strategic, across all phases of the budget cycle, and for making greater progress toward UHC. Actions need to be accompanied by measures to address bottlenecks in the public financial management system.